Implementasi Aplikasi Web untuk Basis Data Disabilitas di National Paralympic Committee of Indonesia Kalimantan Barat: Implementation of Web Application for Database on National Paralympic Committee of Indonesia Kalimantan Barat - Insani, Rachmat Wahid Saleh; Alamsyah, Dedi; Sucipto, Sucipto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The National Paralympic Committee of Indonesia (NPCI) in West Kalimantan is an organization tasked with supporting athletes with disabilities. It supervises training initiatives, manages competition registrations, improves welfare, cultivates character, and ensures the health standards of athletes with disabilities. This agency oversees the data of athletes with disabilities, presently documented on handwritten records maintained in filing cabinets. This community service initiative develops a web application for NPCI West Kalimantan to facilitate the management of data about athletes with impairments. The application has been deployed using hosting services, guaranteeing that the application files are hosted on a web server and own a domain name. This web application has facilitated NPCI West Kalimantan in accessing, adding, modifying, and deleting data about athletes with impairments.